Environmental Performance Reviews: Slovenia - United Nations (United Nations, 1997)
Slovenia has long taken a keen interest in its environment. However gradual environmental deterioration in the eighties posed serious threats to human health and to development. This review presents an in-depth study of Slovenia’s environmental position today. It looks into the framework for environmental policy and management, management of pollution and of natural resources and the economic and sectoral integration. It compliments its findings with a set of draft recommendations which can be used to alleviate environmental problems.